DEVELOPING WRITING SKILL OF EFL LEARNERS AT THE ACCOUNTING DEPARTMENT STIE PANCA BHAKTI PALU THROUGH PROCESS-BASED WRITING - Kuliahana, Ana (Fakultas tarbiyah dan Ilmu Keguruan Institut Agama Islam Negeri Palu, 2016)
This research was designed as a collaborative action research. The subject of this research was 24 EFL students of Accounting Department (AK1) at the first semester of 2015/2016 academic year. The action research was conducted in two cycles where each cycle consisted of planning, implementation, observation, and reflection. Each cycle consists of three meetings. Data was collected through observation sheets and field-notes, marking scheme and students’ writing performance during the implementation of action. The findings of the research show that Process-based writing strategy was effective to improve students’ writing skills in descriptive paragraphs. The effect of this strategy was supported by the classical percentage of students’ from 13 students (52%) who got scores equal or greater than 70 in cycle 1 to become 21 students (84%) who got scores equal or greater than 70 in cycle 2. In addition, Process-based process as a teaching strategy in teaching writing skills was effective to improve students’ writing skills.